2007
DOI: 10.1002/dneu.20379
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal recruitment in adult zebra finch brain during a reproductive cycle

Abstract: Previous studies suggest that adult neurogenesis and neuronal replacement are related to the acquisition of new information. The present study supports this hypothesis by showing that there is an increase in new neuron recruitment in brains of adult male and female zebra finches that coincides with the need to memorize vocalizations of nestlings before they fledge. We counted [(3)H]-Thymidine labeled neurons 40 days after [(3)H]-Thymidine injections. These counts were made in the parents' brains at the time eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 75 publications
(89 reference statements)
2
20
0
Order By: Relevance
“…However, this had already been tested and proven to be the case in three previous studies (Lipkind et al, 2002;Barnea et al, 2006;Barkan et al, 2007) for all three brain regions. Moreover, a previous study from our laboratory further confirmed this outcome for NC, this time by using tissue which was treated with the neuronal marker Hu, just as was done with our present material (M. Pnini, L. Lotem, F. Nottebohm, and A. Barnea, unpublished data).…”
Section: Methodsmentioning
confidence: 93%
“…However, this had already been tested and proven to be the case in three previous studies (Lipkind et al, 2002;Barnea et al, 2006;Barkan et al, 2007) for all three brain regions. Moreover, a previous study from our laboratory further confirmed this outcome for NC, this time by using tissue which was treated with the neuronal marker Hu, just as was done with our present material (M. Pnini, L. Lotem, F. Nottebohm, and A. Barnea, unpublished data).…”
Section: Methodsmentioning
confidence: 93%
“…Adult neuron addition has been studied in HVC, Area X in the AFP, and the auditory region NCM (Lipkind et al, 2002; Barnea et al, 2006; Barkan et al, 2007; Adar et al, 2008b). However, the most intensive study has focused on HVC, with particular interest in the replacement of HVC neurons that project to RA.…”
Section: Neuronal Attributes That Co-vary With Song Attributesmentioning
confidence: 99%
“…In both bird orders neuronal recruitment occurs in the HA (current study; Hoshooley et al, 2005), HC (current study; Barnea and Nottebohm, 1994), Medial striatum (former named Lobus parolfactorius - LPO; Alvarez-Buylla et al, 1994; Ling et al, 1997), NC (Ling et al, 1997; Barkan et al, 2007) and NCL (current study; Barkan et al, 2014). However, other brain regions exhibit neuronal recruitment in one of the two above orders, but are less developed or absent in the other.…”
Section: Discussionmentioning
confidence: 65%